XVIII April International Academic Conference on Economic and Social Development, National Research University Higher School of Economics, Moscow, 11–14 April 2017 - Редакции, Коллектив (Journal of Economic Sociology, 2017)
On April 11–14, 2017, National Research University Higher School of Economics (HSE), with the support of the World Bank, will be holding the XVIII April International Academic Conference on Economic and Social Development in Moscow. The Conference Programme Committee is chaired by Professor Evgeny Yasin.